Research Article In-vitro Anti-dermatophytic Activity of Different Medicinal Plant Extracts: Anti-dermatophytic activity - Kaur, Sandeep; Kaur Gill, Prabhjot (International Journal of Indigenous Herbs and Drugs, 2023)
Background: Dermatophytosis is most common superficial skin infection and dermatophytes are fungi that invade within keratinized tissues; skin, hair and nails. In many studies reported that some medicinal plant are very useful to treat various skin disease included dermatophyte, because these medicinal plants are natural so have low cost, high availability, few side effects and valuable resources. Objective: To evaluate the antifungal activity of Melaleuca alternifolia, Zingiber officinale, Allium sativum, Azadirachta indica, Citrus limonum, Curcuma longa, and Cocos nucifera against the different dermatophytes causing skin infections. Methods: The Melaleuca alternifolia (tea tree oil), Azadirachta indica (neem oil), Cocos nucifera (coconut oil) and fresh juice of Citrus limonum (Lemon) and aqueous extracts of Zingiber officinale, Allium sativum and Curcuma longa were explored for antifungal susceptibility testing as per CLSI guidelines by agar well diffusion method. Results: Anti-fungal potentials of the oils and aqueous extracts of different medicinal plants were tested against Trichophyton mentagrophytes, T. rubrum, T. tonsurans, T. verrucosum, Epidermophyton floccosum, Microsporum gypseum, M. canis. All the seven dermatophytes were susceptible to Melaleuca alternifolia, Zingiber officinale and Allium sativum, showed inhibitory zone ranges from 40±2.0mm to 45±2.0mm. Whereas, Azadirachta indica showed inhibitory zone ranges from 18±2.0 mm to 35±2.0mm for all the seven dermatophytes followed by Citrus limonum. On the contrary Curcuma longa and Cocos nucifera not effective against any tested dermatophytes. Conclusion: The current research provides a scientific validation for the use of these medicinal plants in the treatment of dermatophytic infection and could be used in future for dermatophytic infection and other skin infection.